THE APPLICATION OF ISLAMIC EDUCATION MANAGEMENT IN MAJELIS TAKLIM ACTIVITIES BAITURRAHIM CIMANGGIS DEPOK - Manaf, Abdul (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
This study discusses implementing Islamic education management in the activities of the Baiturrahim Taklim Assembly in Cimanggis, Depok. Islamic education management focuses on the management of learning activities based on Islamic values and aims to improve religious understanding and shape the religious character of participants. It is important to examine how Majelis Taklim Baiturrahim Cimanggis Depok can overcome these challenges by implementing good educational management strategies. With proper management, it is expected that this taklim assembly can continue to play a role as an effective center for religious education and guidance, as well as being able to improve the quality of understanding and practice of religion of the congregation. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The study results indicate that implementing Islamic education management in the Baiturrahim Taklim Assembly includes planning a structured study program, organizing competent educators, implementing activities that focus on studying the Qur'an and Hadith, and routine evaluation of participant participation and understanding. This implementation is effective in building an active learning community oriented towards improving morals and strengthening Islamic brotherhood in the surrounding environment. However, several challenges in terms of funding and facilities still require more attention to improve the quality of the taklim assembly activities.